2017
DOI: 10.1186/s12891-017-1528-y
|View full text |Cite
|
Sign up to set email alerts
|

Silent progression in patients with rheumatoid arthritis: is DAS28 remission an insufficient goal in RA? Results from the German Remission-plus cohort

Abstract: BackgroundRemission is arguably the ultimate therapeutic goal in rheumatoid arthritis (RA). Applying modern strategies, clinical remission can be achieved in a substantial number of patients with early RA (ERA). Even in those patients, the number and scope of erosions can increase. We, therefore, investigated the value of MRI for the detection of radiological progression in patients with DAS28 improvement and/or clinical remission of the German Remission-plus cohort.MethodsData-sets of 80 RA patients (accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 30 publications
1
29
0
2
Order By: Relevance
“…Gal-9 has been suggested to play a role in RA pathogenesis, but the underlying mechanisms have not been elucidated. Previous studies suggest that the measurement of disease activity alone is not sufficient to identify fast progressing RA and high titers of ACPA could be a risk factor for RA progression [21,22]. The correlation between Gal-9 and ACPA observed in our study may suggest that high titers of ACPA may be linked to the rheumatoid inflammatory process through the Gal-9-mediated bone effects indirectly.…”
Section: Discussionmentioning
confidence: 46%
“…Gal-9 has been suggested to play a role in RA pathogenesis, but the underlying mechanisms have not been elucidated. Previous studies suggest that the measurement of disease activity alone is not sufficient to identify fast progressing RA and high titers of ACPA could be a risk factor for RA progression [21,22]. The correlation between Gal-9 and ACPA observed in our study may suggest that high titers of ACPA may be linked to the rheumatoid inflammatory process through the Gal-9-mediated bone effects indirectly.…”
Section: Discussionmentioning
confidence: 46%
“…Eighteen percent of individual patients did, however, show significant (≥SDC) progression of erosion score. With only two time-points for imaging (screening/baseline and Week 24), it cannot be known whether these structural changes represented progression of disease despite treatment—progression has been reported in other studies, despite clinical remission [14, 15]—or if the structural changes observed at Week 24 actually developed only during the initial period of treatment prior to TCZ reaching its maximum inhibitory effect. Additional time-points would be needed to determine this and whether residual inflammation visible at Week 24 was sufficient to keep joint damage progressing (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Dabei befindet sich der Patient außerhalb des Hauptmagnetfeldes und lediglich die Hand wird innerhalb des Magneten gelagert. Der im Vergleich zum HF-MRT niedrigeren Ortsauflösung zum Trotz, können mittels NF-MRT vergleichbare Aussagen zu Erosionen, Synovialitis und Therapieansprechen getroffen werden [17][18][19][20]. Bei einem zudem deutlich niedrigeren Anschaffungspreis sind NF-Scanner in Wissenschaft und Praxis von zunehmendem Interesse.…”
Section: Technische Voraussetzungenunclassified